Challenges for Transforming Family Planning Rights into Practices in Nepal - Shrestha, Khadga Bahadur (Health Prospect, 2014)
Transforming family planning rights into practices is not an easy task especially in a developing nation like Nepal where society is patriarchal and literacy is low. Besides, coverage and quality of reproductive health services and active involvement of the community is crucial in the transformation. For properly addressing these challenges, all the sectors that provide family planning services need to act on advocacy, creating demand, reshaping service delivery, sustainability (financial and self-reliance) and high level political and financial commitments are necessary. DOI: http://dx.doi.org/10.3126/hprospect.v12i2.9874 Health Prospect Vol.12(2) 2013: 42-46